2021
DOI: 10.3390/ma14010228
|View full text |Cite|
|
Sign up to set email alerts
|

Four-Fold Multi-Modal X-ray Microscopy Measurements of a Cu(In,Ga)Se2 Solar Cell

Abstract: Inhomogeneities and defects often limit the overall performance of thin-film solar cells. Therefore, sophisticated microscopy approaches are sought to characterize performance and defects at the nanoscale. Here, we demonstrate, for the first time, the simultaneous assessment of composition, structure, and performance in four-fold multi-modality. Using scanning X-ray microscopy of a Cu(In,Ga)Se2 (CIGS) solar cell, we measured the elemental distribution of the key absorber elements, the electrical and optical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…It has been found that the XEOL intensity of the DA and the excitonic emission becomes stronger by about 30% when the excitation X-ray energy varies from 8929 eV (E K À 50 eV) to 9029 eV (E K + 50 eV) across the Cu K-edge. Although XEOL intensity maps with nanoscale spatial resolution measured at 15.25 keV (just above the Rb K-edge) have been reported for Cu(In,Ga)Se 2 solar cells (Ossig et al, 2021), to our knowledge, we present here for the first time energy-resolved XEOL spectra of chalcopyrite CuInSe 2 material measured at different excitation X-ray energies.…”
Section: Nir-xeol: a Case Study On Cuinsementioning
confidence: 94%
See 1 more Smart Citation
“…It has been found that the XEOL intensity of the DA and the excitonic emission becomes stronger by about 30% when the excitation X-ray energy varies from 8929 eV (E K À 50 eV) to 9029 eV (E K + 50 eV) across the Cu K-edge. Although XEOL intensity maps with nanoscale spatial resolution measured at 15.25 keV (just above the Rb K-edge) have been reported for Cu(In,Ga)Se 2 solar cells (Ossig et al, 2021), to our knowledge, we present here for the first time energy-resolved XEOL spectra of chalcopyrite CuInSe 2 material measured at different excitation X-ray energies.…”
Section: Nir-xeol: a Case Study On Cuinsementioning
confidence: 94%
“…In parallel, the I 0 signal is measured at the first ionization chamber which ensures both the monitoring of the incident X-ray beam flux and the normalization of the XEOL intensity probed at each X-ray energy. The XEOL signal can also be measured in the absence of the X-ray beam or even the sample to investigate the presence of various artifacts in the XEOL spectrum due to the scattering light effects in the experimental hutch (Ossig et al, 2021) or possible emission from the cryostat windows, holders, substrates, etc. Once these measurements are completed and typical exposure times are determined, the XEOL and XAFS spectra are detected simultaneously during an X-ray energy scan across the specific X-ray energy region of interest.…”
Section: Xeol Measurementsmentioning
confidence: 99%
“…[13][14][15][16] Analytical techniques, such as X-ray uorescence (XRF), X-ray diffraction, ptychography and X-ray beam induced current (XBIC), applied simultaneously can provide spatially correlated information between the chemical composition and electrical properties of the specimen without destroying it. [17][18][19][20][21][22] However, such information is oen not sufficient to understand the limitations of energy-harvesting devices. The complex architecture of the new generation solar cells comprising multiple layers makes it hard to determine the fundamental mechanisms impacting the electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, XRF and XBIC mapping can be performed simultaneously to capture direct spatial correlations between nanoscale defects and their effects on local charge collection 10,23,30 . Recently, these techniques have successfully been extended to include four modalities 31 under normal (25 • C, nominal humidity) laboratory conditions. Sample stages have been developed that are both compatible with synchrotron X-ray facilities and can measure material properties in-situ [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%